THE COMPARISON OF TABOO WORDS AND SWEARWORDS USED BY MEN AND WOMEN OF SUKU ANAK DALAM IN DESA BALAI RAJO - Megika Fajri; Hermawati Syarif; Fitrawati Fitrawati (English Language and Literature, 2018)
The aims of this research is to describe the types of taboo words and types and functions of swearwords used by men and women of Suku Anak Dalam, the differences of swearwords used by men and women. The type of this research was a descriptive qualitative research. The data were the taboo words and swearwords used by the informants. The informants were (men and women) of Suku Anak Dalam. The data were collected by using interview method with stimulation technique. It is found there are five types of taboo words used by men. Meanwhile, there two types of taboo words used by women. It is also found there are six types of swearwords used by men. They are swearwords from sex organs, minor (animals and diseases), mother type, body function, scatology and religious. Meanwhile, swearwords used by women are only three. They are sex organ, minor (animal) and religious. Swearwords have various functions in Suku Anak Dalam.  For men, there are three functions of swearwords, expletive, abusive, and humoristic. Meanwhile, for women there are two functions of swearwords, abusive and expletive. In short, men have more various types of taboo words and swearwords than women. Men mostly use the type of sex organs for the taboo words and swearwords, ruder and impolite than women’s. While, women have fewer types of taboo words and swearwords. Men use swearwords to abuse and mostly to express anger. Meanwhile women use abusive function to express anger and disappointment.